Disentangling the photochemical salinity tolerance in Aster tripolium L.: connecting biophysical traits with changes in fatty acid composition. (13th November 2016) - Duarte, B.; Cabrita, M. T.; Gameiro, C.; Matos, A. R.; Godinho, R.; Marques, J. C.; Caçador, I.
Abstract: A profound analysis of A. tripolium photochemical traits under salinity exposure is lacking in the literature, with very few references focusing on its fatty acid profile role in photophysiology. To address this, the deep photochemical processes were evaluated by Pulse Amplitude Modulated (PAM) Fluorometry coupled with a discrimination of its leaf fatty acid profile. Plants exposed to 125–250 mm NaCl showed higher photochemical light harvesting efficiencies and lower energy dissipation rates. under higher NaCl exposure, there is evident damage of the oxygen evolving complexes (OECs). On the other hand, Reaction Centre (RC) closure net rate and density increased, improving the energy fluxes entering the PS II, in spite of the high amounts of energy dissipated and the loss of PS II antennae connectivity. Energy dissipation was mainly achieved through the auroxanthin pathway. Total fatty acid content displayed a similar trend, being also higher under 125–250 mm NaCl with high levels of omega‐3 and omega‐6 fatty acids. The increase in oleic acid and palmitic acid allows the maintenance of the good functioning of the PS II. Also relevant was the high concentration of chloroplastic C16:1t in the individuals subjected to 125–250 mm NaCl, related with a higher electron transport activity and with the organization of the Light Harvesting Complexes (LHC) and thus reducing the activation of energy dissipation mechanisms. All these new insights shed some light not only on the photophysiology of this potential cash‐crop, but also highlight its important saline agriculture applications of this species as forage and potential source of essential fatty acids.